FRI0573 Ultrasonography and histological diagnosis concordance in patiens with suspected primary sjÖgren syndrome. (12th June 2018) - Barrio Nogal, L.; Bohórquez, C.; Perez Gómez, A.; Castelló, A.; León, M.J.; Pretel, P.; Álvarez de Mon, M.
Abstract : Background: Minor salivary gland biopsy (MSGB) is the most used diagnostic tool for primary Sjögren Syndrome (SS). The potential relevance of an alternative non-invasive, fast, low cost and choice by the patient technique, like mayor salivary gland ultrasonography (MSGUS), has to be investigated. Objectives: To evaluate the utility of MSGUS as a diagnostic tool for primary SS and to study the concordance with MSBG. Methods: 36 patients were consecutively recruited with clinical and/or analytical suspicion of SS, from outpatient Rheumatology consultations from 2015–2017. All patients received a MSGB and a MSGUS. Two echographers performed two images readings with an interval of at least one week. They worked blinded for clinical and histological results. Demographics, clinical, serological, ESSPRI and ESDAI were recorded. The histological results were classified according to Chisholm and Mason score and the US results according to the system by Cornec et al . The final SS diagnosis was made using the 2002 classification criteria. Subsequently the data was analysed using the statistical software STATA/MP. Adjusted concordance intra and interobserver (kappa coefficient) was calculated for the diagnoses performed by US (normal/pathological). The validity of US and biopsy to diagnose SS according to the 2002 criteria was evaluated by calculating the percent agreement between the tests, along with the specificity, sensitivity, PPV, NPV and area below the curve (AUC). Further, the percent association of the diagnoses between serology and US were determined, and the statistical significance of it was evaluated with chi-square test. Results: 94% were female, with an average age of 58 years. 69% were non-smokers. 89% showed pathological Shirmer test, 78% extraglandular features, 19% hypocomplemetemia and 44% hypergammaglobulinemia. As for the serological data, 81% had positive ANAS, 44% antiRo52, 39% antiRo60% and 28% antiLa. 39% of the patients were RF positive. 69% fulfilled the 2002 classification criteria with an average ESSPRI of 5.3 and ESSDAI of 1.5. Using these criteria as a gold-standard, the total percentage agreement was 83.3% for US and 80.6% for biopsy (S 92, Sp 64.3%). A good concordance was found between both observers (kappa=0.8) along with intraobserver (kappa=0.64 and 0.78 for first and second observer respectively). The percentage of patients with positive antibodies (48% antiRo52, 41% antiRo60, 30% antiLa) had pathological US. Significant statistical differences were not found in patients with normal US (p>0.44 in all associations explored). Conclusions: MSGUS is a non-invasive imaging method useful for the diagnosis of primary SS in common clinical practice with a diagnostic value similar to the MSGB. MSGUS has good correlation intra and interobserver. There was no statistical significant association found between the positive autoimmune antibodies and US. References: [1] Is salivary gland ultrasonography a useful tool in Sjögren's syndrome? A systematic review. Sandrine Jousse-Joulin Rheumatology (Oxford)2016May;55(5):789–800. [2] Mossel E, et al. Ultrasonography of major salivary glands compared with parotid and labial gland biopsy and classification criteria in patients with clinically suspected primary Sjögren's syndrome. Ann Rheum Dis2017. Disclosure of Interest: None declared